DMD transcript imbalance determines dystrophin levels. Issue 12 (23rd August 2013) - Spitali, Pietro; van den Bergen, Janneke C.; Verhaart, Ingrid E. C.; Wokke, Beatrijs; Janson, Anneke A. M.; van den Eijnde, Rani; den Dunnen, Johan T.; Laros, Jeroen F. J.; Verschuuren, Jan J. G. M.; Hoen, Peter A. C. 't; Aartsma‐Rus, Annemieke
Abstract : Duchenne and Becker muscular dystrophies are caused by out‐of‐frame and in‐frame mutations, respectively, in the dystrophin encoding DMD gene. Molecular therapies targeting the precursormRNA are in clinical trials and show promising results. These approaches will depend on the stability and expression levels of dystrophin mRNA in skeletal muscles and heart. We report that the DMD gene is more highly expressed in heart than in skeletal muscles, in mice and humans. The transcript mutated in the mdx mouse model shows a 5′ to 3′ imbalance compared with that of its wild‐type counterpart and reading frame restoration via antisense‐mediated exon skipping does not correct this event. We also report significant transcript instability in 22 patients with Becker dystrophy, clarifying the fact that transcript imbalance is not caused by premature nonsense mutations. Finally, we demonstrate that transcript stability, rather than transcriptional rate, is an important determinant of dystrophin protein levels in patients with Becker dystrophy. We suggest that the availability of the complete transcript is a key factor to determine protein abundance and thus will influence the outcome of mRNA‐targeting therapies.—Spitali, P., van den Bergen, J. D., Verhaart, I. E. C., Wokke, B., Janson, A.A.M., van den Eijnde, R., den Dunnen, J. T., Laros, J. F. J., Verschuuren, J. G. M., 't Hoen, P. A. C., Aartsma‐Rus, A., DMD transcript imbalance determines dystrophin levels. FASEB J. 27, 4909–4916 (2013). www.fasebj.org